Navigating Pronoun-Antecedent Challenges: A Study of ESL Academic Writing Errors - Shengji Li; Huma Akram (SAGE Open)
Effective communication and academic writing in English hinge on a solid grasp of grammar, with pronouns representing a pivotal aspect. However, non-native, particularly English as a second language (ESL) students, often find difficulties in employing pronouns effectively, especially in reference to their antecedents within sentences. The current study investigates errors in pronoun-antecedent agreement among ESL students in their academic writing by employing content analysis. By using purposive sampling technique, 40 students from four universities in Karachi city were selected and assigned to write a paragraph on any personality they are familiar with. Subsequently, all of the writing samples were examined thoroughly utilizing a systematic approach. The analysis revealed that errors predominantly occurred with personal pronouns, followed by possessive pronouns, relative pronouns, and demonstrative pronouns. While this study offers valuable insights into the difficulties ESL students face in mastering pronoun-antecedent agreement, it is essential to note limitations. The sample size may not fully represent the diverse range of ESL students, and the focus on academic writing may not capture all contexts in which pronoun-antecedent agreement challenges arise. Despite these limitations, the findings provide important considerations for ESL teachers. The implications of these findings extend to the design of effective language instruction, aimed at enhancing students’ writing skills and mitigating common pronoun-antecedent agreement errors.